Physical Activity: COVID-19 Enemy (Archives of Clinical and Medical Case Reports, 2021)
For much of mankind, the COVID-19 pandemic created an extraordinary condition, with a severe impact on almost all domains of life. Physical activity (PA) was no exception, and disturbing findings showing the deleterious effect of lockdown measures on PA were recorded in relevant studies conducted in several different countries. It appears that society has overlooked or underestimated the advantages of PA in developing a defense against the virus and the incremental trend of non-communicable diseases (NCDs), and the prevalence of physical inactivity has presented many major challenges to public health authorities. In this article, in the presence of COVID-19, we briefly remember and highlight the beneficial impact of a physically active life and daily exercise training on public health, even more so for the most vulnerable groups. In this respect, we should not underestimate the role of PA and non-exhaustive exercise as a countermeasure and an indirect therapeutic agent against the virus, as well as against NCDs and mental health issues arising from the COVID-19 crisis.